In Search of the Ancient Maya Foods. A Paleoethnobotany Study From a Non-elite Context in Sihó, Yucatán - Herrera-Parra, Esteban Moisés (Ethnobiology Letters, 2023)
Food consumption is one of the primary activities of all cultural groups around the globe. The procurement of plants, their transformation, and consumption are some steps in which we can identify social repercussions such as identity, gender roles, labor division, worldview, and status differentiation, among many other archaeological approaches. In the Northern Maya Lowlands, paleoethnobotany research has included information regarding the consumption of plants by the ancient Mayas, which has helped us to broaden our knowledge about past feeding habits; nonetheless, we recognize some of the dishes and plants consumed by the elites due to the epigraphy and iconography records. It is least known what the commoners consumed during their day-to-day meals. In this vein, this research is immersed in identifying plants exploited by two low-strata domestic groups in the archaeological site of Siho, Yucatan, Mexico, during the Late-Terminal Classic. Through the recognition of starches recovered from soil samples, some staple crops like maize (Zea mays) and beans (Phaseolus spp.) were identified. More importantly, other plants least representative in the archaeobotanical record, like arrowroot (Maranta arundinacea), and Mexican yam (Pachirhyzus erosus), were also recognized. This research contributes to the identification and study of starches that generates information for the broad discussion of food-related activities in non-elite household contexts.